2013
DOI: 10.1159/000346343
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Usefulness of Multifrequency Tympanometry for Ménière’s Disease

Abstract: Multifrequency tympanometry (MFT) is the measurement of the impedance of the middle ear transmission system at a wide range of frequencies from 200 Hz to 2 kHz. A potential use of MFT as a new diagnostic tool for detecting endolymphatic hydrops has recently been reported. However, its clinical usefulness for diagnosing Ménière’s disease (MD) remains unclear. To evaluate the clinical usefulness of MFT as a new qualitative and diagnostic test for MD, we performed MFT in 70 patients with unilateral or bilateral M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
28
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 77 publications
6
28
0
1
Order By: Relevance
“…In the preliminary study of Franco-Vidal et al, 11 RF level in the symptomatic ears of 40 patients with Ménière’s was measured as 752 Hz while this level was 820 Hz in asymptomatic ears. Sugasawa et al 12 confirmed the previous results in their study conducted on Ménière’s disease patients. Although endolymphatic fluid increase is not at pathological level during pregnancy, a similar mechanism that occurred in Ménière’s disease can also be mentioned in pregnant women.…”
Section: Discussionsupporting
confidence: 74%
“…In the preliminary study of Franco-Vidal et al, 11 RF level in the symptomatic ears of 40 patients with Ménière’s was measured as 752 Hz while this level was 820 Hz in asymptomatic ears. Sugasawa et al 12 confirmed the previous results in their study conducted on Ménière’s disease patients. Although endolymphatic fluid increase is not at pathological level during pregnancy, a similar mechanism that occurred in Ménière’s disease can also be mentioned in pregnant women.…”
Section: Discussionsupporting
confidence: 74%
“…The apparent increase in RF with increasing body tilt was unexpected (although this result was not statistically significant), as previous studies in MD patients have reported a clear decrease in RF between attacks (6,12). RF corresponds to the equilibrium between the rigidity and the mass of the components of the middle and inner ears.…”
Section: Discussionmentioning
confidence: 55%
“…In recent years, three studies have confirmed these findings (12Y14). In 2013, Sugasawa et al (12) used admittance to demonstrate the same decrease in RF and the same increase in width tympanograms in MD patients compared with controls. As in our study, the MD patients were tested outside an attack (6).…”
mentioning
confidence: 99%
“…It has been proposed that increased endolymph space alters the mechanical impedance of the stapes footplate, leading to the "third-window" effect, which may reduce the RF of the middle ear [14] . Multi-frequency tympanometry is also used as a simple, noninvasive, complementary test in the diagnosis of endolymphatic hydrops [15] . Considering these wide applications of the components of multi-frequency tympanometry, its test-retest reliability was assessed for determining efficient clinical application of these measures.…”
Section: Discussionmentioning
confidence: 99%